Implementasi Nilai Inovator KejarAURORA Bagi Anak-Anak Pra Sejahtera - Puji Prabowo; Farida Iriani (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Many problems in Indonesia need to be solved by innovations. Creating innovators is believed as the way of giving solutions for the future. However, creating innovators need to be prepared since the early years. Started in 2012, a non-profit organization named kejarAURORA provides non-formal education for the underprivileged children to learn skills freely. KejarAURORA aims to increase the quality of human resources and create innovator as the change agent of Indonesia in the future. Learning activities are conducted based on curriculum written by kejarAURORA team. Positive changes from the children as learning participants and parents are used as evaluation tools. Response towards activities, personal development, and positive impacts happening on school become three main aspects that evaluated from the children. While for parents, their children's learning attitudes, skills, and knowledge received during participation in kejarAURORA are evaluated. Positive impacts also found from the volunteer teachers about direct learning from the kids, self-development, understanding the happiness, as well as being grateful. In addition, some media interviews and inspirational talks were done to deliver the progress and impacts of this program. Overall, kejarAURORA has been giving positive impacts toward its participants.